PENGARUH KOMITMEN ORGANISAI DAN KETERLIBATAN KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA HOTEL RESTY MENARA PEKANBARU) - Putri, Engla Dika; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to analyze the organizational commitment and job involvement and influence on the performance of employees at Resty Menara Hotel Pekanbaru. Organizational Commitment as a variable (X1), Work Involvement as a variable (X2), and employee performance as a variable (Y). The method in this research is descriptive and quantitative using SPSS 21, wherein the samples used are 63 employees who conducted the census and data collection through questionnaires. The results of the analysis using the validity, reliability, determination test, simple linear regression, multiple linear regression test, t test and F. It can be concluded that organizational commitment significantly influence the performance of employees at Resty Menara Hotel Pekanbaru, work engagement significantly influence performance of employees at Resty Menara Hotel Pekanbaru, and commitment, and job involvement oganisasi significant effect on the performance of employees at Resty Menara Hotel Pekanbaru. Keywords: Organizational Commitment, Job Involvement and Employee Performance